TOXICITY RESEARCH OF SOME SPIROHYDANTOIN DERIVATIVES TOWARDS LUMBRICUS TERRESTRIS: TOXICITY RESEARCH OF SOME SPIROHYDANTOIN DERIVATIVES TOWARDS LUMBRICUS TERRESTRIS - Ganchev, Donyo; Marinov, Marin; Stoyanov, Neyko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This paper presents an ecotoxicological examination of cyclopentanespiro-5-hydantoin, cyclopentanespiro-5-(2,4-dithiohydantoin) and 1-aminocyclopentane-1-carboxylic acid towards Lumbricus terrestris – the common earthworms which are extremely important for the ecological stability and fertility of soils.